Effect of Copperoxychloride on the Fermentation of Must and on Wine Quality - Tromp, A.; de Klerk, C.A. (South African Journal of Enology and Viticulture, 2017)
A Chenin blanc and a Colombar vineyard was sprayed with copperoxychloride (CuOCI) in different spraying programs. A laboratory trial was conducted where copper in different concentrations was added to grape must and fermented. Copper concentrations were determined in musts and wines, fermentation curves established and wine quality assessed. Results show that spraying a vineyard with CuOCI for 5 or 6 consecutive sprays up to 14 or 3 days before harvest respectively caused copper concentrations of 13-44 mg// in the settled musts. Spraying a vineyard at 14 + 7 + 3 days before harvest yielded a must with a copper concentration of 16 mg//. These musts as well as a must to which 10 mg/ I of copper was added, underwent slower fermentation than their respective controls. Wine quality was seriously impaired. It is concluded that the closer to harvest the last copper spray is applied, the more problems will be encountered.